The Effect of the Effectiveness of Sustenance Social Assistance and Accompaniment on the Prosperity of Pre Prosperous Society in Tanjung Pura District Langkat Regency - M. Hidayat; Erika Revida; Badaruddin Badaruddin (Budapest International Research and Critics University, 2021)
The aim of this study is to analyze the effect of effectiveness of sustenance social assistance and accompaniment on the prosperity of pre prosperous society in Tanjung Pura Subdistrict, langkat regency, analyze the effect of effectiveness of sustenance social assistance and accompaniment on the prosperity of pre prosperous society in Tanjung Pura District, Langkat Regency and analyze the effect of effectiveness of sustenance social assistance and accompaniment in common on the prosperity of pre prosperous society in Tanjung Pura District, Langkat Regency. This research was conducted in Langkat Regency about the effect of effectiveness of sustenance social assistance and accompaniment on the prosperity of pre prosperous society in Tanjung Pura District, Langkat Regency. The analysis method of this research is multiple regression analysis with the total respondent of 100 beneficiary families. The result of this research showed that there is positive and significant effect of the effectiveness of sustenance social assistance on the prosperity of pre prosperous society in Tanjung Pura District. At the same time of the effectiveness of sustenance social assistance and accompaniment has positive and significant effect.